2020
DOI: 10.1101/2020.10.14.20212795
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Sensitive, Rapid, and Portable CasRx-based Diagnostic Assay for SARS-CoV-2

Abstract: Since its first emergence from China in late 2019, the SARS-CoV-2 virus has spread globally despite unprecedented containment efforts, resulting in a catastrophic worldwide pandemic. Successful identification and isolation of infected individuals can drastically curtail virus spread and limit outbreaks. However, during the early stages of global transmission, point-of-care diagnostics were largely unavailable and continue to remain difficult to procure, greatly inhibiting public health efforts to mitigate spre… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 89 publications
1
13
0
Order By: Relevance
“…A PPA of 57% and NPA of 100% were obtained when the performance of the SENSR targeting the N gene was evaluated with 21 positive and 21 negative SARS-CoV-2 clinical samples. This proof-of-concept work by Brogan et al [71] demonstrated the potential of utilizing Cas13d in CRISPR-Dx and highlights the possibility of combining Cas13d with other Cas proteins that lack poly-U preference for multiplex detection [71]. However, the low diagnostic sensitivity of SENSR indicated that further optimization is required.…”
Section: Cas13d-based Assaymentioning
confidence: 98%
See 1 more Smart Citation
“…A PPA of 57% and NPA of 100% were obtained when the performance of the SENSR targeting the N gene was evaluated with 21 positive and 21 negative SARS-CoV-2 clinical samples. This proof-of-concept work by Brogan et al [71] demonstrated the potential of utilizing Cas13d in CRISPR-Dx and highlights the possibility of combining Cas13d with other Cas proteins that lack poly-U preference for multiplex detection [71]. However, the low diagnostic sensitivity of SENSR indicated that further optimization is required.…”
Section: Cas13d-based Assaymentioning
confidence: 98%
“…The sensitive enzymatic nucleic-acid sequence reporter (SENSR) differed from the abovementioned CRISPR-Cas13-based assays for SARS-CoV-2 detection as the platform uses RfxCas13d (CasRx) from Ruminococcus flavefaciens. Similar to LwaCas13a, Cas13d is an RNA-guided RNA targeting Cas protein that does not require PFS and exhibits collateral cleavage activity upon target RNA binding, but Cas13d is ~20% smaller than Cas13a-Cas13c effectors [71]. SENSR is a two-step assay that consists of RT-RPA to amplify the target N or E genes of SARS-CoV-2 followed by T7 transcription and CasRx assay.…”
Section: Cas13d-based Assaymentioning
confidence: 99%
“… 20 , 22 24 , 27 Different Cas13 variants are used for nucleic acid detection. For example, Cas13a, 21 , 39 Cas13b, 40 and Cas13d 41 exhibit collateral cleavage activities and work for nucleic acid detection. Here, we sought to expand the Cas13-based toolbox for diagnostic applications by identifying and characterizing novel CRISPR/Cas13 effectors.…”
Section: Introductionmentioning
confidence: 99%
“…Cas13d has a remarkably compact protein size, and one ortholog derived from Ruminococcus flavefaciens XPD3002 (RfxCas13d) has highly efficient, robust, specific RNA interference activity in both mammals and plants (Konermann et al, 2018;Kushawah et al, 2020;Mahas et al, 2019;Yan et al, 2018;Zhou et al, 2020). The collateral activity of RfxCas13d was recently developed as a diag-nostic tool for SARS-CoV-2 (Brogan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%